The interrelationship between attentional and executive deficits in major depressive disorder. (1st April 2016) - Nilsson, J.; Thomas, A. J.; Stevens, L. H.; McAllister‐Williams, R. H.; Ferrier, I. N.; Gallagher, P.
Abstract : Objective: Cognitive dysfunction is an established feature of major depressive disorder (MDD). However, it remains unclear whether deficits in different cognitive domains are relatively independent or originate from a circumscribed 'primary deficit'. This study tested the hypothesis that a deficit in attention represents a primary deficit in depression. Method: Neuropsychological function was assessed in 30 depressed patients with MDD and 34 control participants. Cognitive composites were derived from a minimum of three tests and included attention, executive function, visuospatial memory and verbal memory. A multivariate analysis of variance was used to assess group differences in overall cognitive performance, and multiple regression models were used to evaluate the role of attention in deficits in other domains. Results: The cognitive deficit in the depressed sample was found to be characterized by poorer performance in attention and executive function. When evaluating the interrelationship between the two deficits, the attentional deficit was found to persist when variability in executive function was statistically accounted for, whilst the executive deficit was eliminated when attention was accounted for. Conclusion: The results demonstrated that the attentional deficit could not be explained by deficits in executive function, which provides support for a primary attention deficit in depression.